2004
DOI: 10.1089/dia.2004.6.567
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Diabetes Through Information Technology: Tools for Monitoring and Control of the Patients' Metabolic Behavior

Abstract: A telemedicine system may incorporate features that make it a suitable technological backbone for implementing a disease management program. The availability of data analysis tools, automated messaging system, and summary indicators of the effectiveness of the health care program may help in defining efficient clinical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…We reviewed the literature on PWP-delivered interventions and disease management support targeting persons with diabetes and or enhancing diabetes care and found that PWP systems enhance patient-provider communication [20, 22, 24, 25], increase overall satisfaction with care [9•, 23••, 26–28], expand access to health information [21, 24, 29, 30], and improve disease management [9•, 26, 27, 29, 3136] and patient outcomes [29, 3234, 36] in diabetes. The recent body of PWP evaluation studies has established the usefulness of PWPs for improving care and clinical outcomes, but many of the studied PWPs have unique functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature on PWP-delivered interventions and disease management support targeting persons with diabetes and or enhancing diabetes care and found that PWP systems enhance patient-provider communication [20, 22, 24, 25], increase overall satisfaction with care [9•, 23••, 26–28], expand access to health information [21, 24, 29, 30], and improve disease management [9•, 26, 27, 29, 3136] and patient outcomes [29, 3234, 36] in diabetes. The recent body of PWP evaluation studies has established the usefulness of PWPs for improving care and clinical outcomes, but many of the studied PWPs have unique functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phone can also provide an additional link between the health care professional and the patient for personalized feedback (eg, reminders, statistics, or medical advices) [9,10,14,16], education [12,13], or motivation [23]. In addition to technical feasibility, several studies have already pointed out the impact on adherence to therapy [11,12] and self-management [10] when mobile phones are used.…”
Section: Introductionmentioning
confidence: 99%
“…Even more advanced systems have been developed in which the data will be translated by the computer and dose adjustments are sent back to the patient with minimal interaction from the health care team. 3 This fully automated program is still being tested. Other web-based applications encourage patients to practice dose adjustments on a simulator, which accounts for insulin sensitivity, type of insulin, dietary intake, and physical activity (AIDIA2).…”
Section: Discussionmentioning
confidence: 99%